Kerem Quality Control Using the Quality Control Circle (QCC) Method at PT. XYZ - Yusita Attaqwa; Wahyu Sidiq Saputra; Ahmad Mustofa Khamal (Institut Teknologi Bisnis AAS Indonesia, 2021)
Abstract - The ‘kerem’ production process is the earliest process of the entire process in iron casting. The brake itself is a mandatory thing in an iron foundry company because it functions as a limiter of the inner diameter of an iron casting product or more simply as a hole in iron casting products. With the analysis carried out using seven tools, it is expected to be able to obtain actual data to improve the quality of brake production, look for factors that affect brake quality, control the number of rejects, countermeasures, repairs, and standardization. The biggest problems with defects in the production of brakes are porous, broken, cracked and not full sand. From the aspect of 4M + 1E, the Man factor is the dominant cause of brake defects. Meanwhile, the number of rejects outside the 2.5% AQL limit was 6 times, namely on 8 July 2021 as many as 16 pcs (AQL 2.5% was at 10 pcs). Then on July 17, 2021 as many as 15 pcs (2.5% AQL at 13 pcs) on July 18 2021 as many as 30 pcs (2.5% AQL at 2 pcs) on July 20 2021 as many as 25 pcs (AQL 2.5% was at 12.63) on 27 July 2021 as many as 20 pcs (AQL 2.5% was at 19 pcs) and finally on August 5, 2021 as many as 30 pcs (AQL 2.5% was at 12.6 pcs).